Quality services and experiences in hospitality and tourism - Cai, Liping A.; Alaedini, Pooya, 1967- (Bridging tourism theory and practice, 2018)
This volume presents the latest perspectives and practices on quality services and experiences in hospitality and tourism. It offers conceptual discourse, empirical evidence, application of existing and emerging theories, and considers the implications of practical findings to extend beyond the academic realm of service quality, and examine the quality issues of both services provided and experiences encountered across a wide spectrum of tourism sectors. As such, it provides new intelligence and contributes to the study of new consumers, as well as organizations and destinations that serve and host them. The book continues the series' tradition of connecting scholarly works and real-world cases, with a unique mix of geographic representations. The majority of its chapters are drawn from the proceedings of the 2016 conference on Service Quality in Hospitality and Tourism: Experiencing Persian Heritage held in Isfahan, Iran. The regional focus of the conference is augmented in this book with contributions from elsewhere, resulting in a more diverse and global context for the treatment of quality services and experiences in hospitality and tourism. The volume will appeal to academic scholars and industry professionals interested in exploring new frontiers of knowledge on the subject. Organized in three parts with distinctive themes, the chapters are appropriate course readings, either collectively or selectively, for undergraduate and graduate students in educational programs focusing on global curricula.